An Item Response Theory Analysis of Algorithms and Programming Concepts in App Inventor Projects - da Cruz Alves, Nathalia; von Wangenheim, Christiane Gresse; Rossa Hauck, Jean Carlo; Ferreti Borgatto, Adriano (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP); 2021: Anais do Simpósio Brasileiro de Educação em Computação, 2021)
Computing education is often introduced in K-12 focusing on algorithms and programming concepts using block-based programming environments, such as App Inventor. Yet, learning programming is a complex process and novices struggle with several difficulties. Thus, to be effective, instructional units need to be designed regarding not only the content but also its sequencing taking into consideration difficulties related to the concepts and the idiosyncrasies of programming environments. Such systematic sequencing can be based on large-scale project analyses by regarding the volition, incentive, and opportunity of students to apply the relevant program constructs as latent psychometric constructs using Item Response Theory to obtain quantitative ?difficulty? estimates for each concept. Therefore, this article presents the results of a large-scale data-driven analysis of the demonstrated use in practice of algorithms and programming concepts in App Inventor. Based on a dataset of more than 88,000 App Inventor projects assessed automatically with the ANON rubric, we perform an analysis using Item Response Theory. The results demonstrate that the easiness of some concepts can be explained by their inherent characteristics, but also due to the characteristics of App Inventor as a programming environment. These results can help teachers, instructional and curriculum designers in the sequencing, scaffolding and assessment design of programming education in K-12.